Penyakit Bulosa Autoimun pada Lanjut Usia: Tinjauan Pustaka - Putra, Gilang Widratama; Saraswati, Putu Dyah Ayu (Cermin Dunia Kedokteran, 2025)
The increase in cases of bullous diseases in the elderly is related to various factors. Aging causes a decline in skin structure and integrity, making it more susceptible to bullous diseases. This disease occurs because the aging process causes immune system dysregulation, which increases the risk of autoimmune conditions. Bullous diseases that commonly occur in the elderly are usually bullous pemphigoid (an autoimmune bullous condition) and pemphigus vulgaris (a skin disease that causes blisters), which are associated with significant morbidity and mortality. Bullous pemphigoid is characterized by tense subepidermal blisters, while pemphigus vulgaris is characterized by loose suprabasal blisters that rupture easily. Histopathological examination and direct immunofluorescence are the gold standard for diagnosis. The management of autoimmune bullous diseases in the elderly is generally the same as for bullous diseases in general, such as corticosteroids and immunosuppressive agents. However, appropriate and effective management is necessary, along with increased attention to the risks of polypharmacy and drug side effects that may cause new problems in elderly patients, including an increased risk of infection, osteoporosis, and metabolic complications.